(untitled) (Journal of the College of Basic Education, 2022)
The research consists of five chapters:The first chapter deals with the methodological framework, which begins with a presentation and formulation of the research problem that sheds light on vocal improvisations in editing the Iraqi maqam and neglecting the role of the performer and not dealing with it in musical scientific studies, which was one of the reasons for writing the research. The researcher determined the importance of his research with the following points:1- It deals with a new topic from an angle that has not been touched on previously.2- It is a research resource that benefits the music library and singing specialists.